Prawne i podatkowe bariery rozwoju sekurytyzacji wierzytelności bankowych w Polsce - Kalasińska, Magdalena (Barriers of Development Securitization in Polish Banks, 2007)
The development of securitization on polish market is no so dynamic as it is possible to expect. The main problem is probably information barrier. It turns out, that many enterprises isn't aware from capability of conducting of securitization. The basic barrier of spread of securitization seems on lack of proper legal regulation, which would facilitate adaptation of this method on polish market, in bank sector particularly. Polish market and particularly banks should regulate, with reference to securitization, such topics like tax, account, transfer of debt, activity of financial institution and turn valuable papers. The paper presents the major problems with securitization on polish market. Particular push has been put on securitization in polish banks and problems related with its preparation and conducting in polish condition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 260-266